Study on the Modification of Polyvinylidene Fluoride Films with Barium Zirconate Titanate to Achieve Excellent Dielectric Property. Issue 42 (8th November 2021) - Qu, Jiale; Gao, Shen; Hou, Zhenghao
Abstract: The barium zirconate titanate coated with dopamine is an excellent dielectric material. Herein, we prepared a type of BaLaZrTiO3 (BLZT) powder by hydrothermal method and coated BLZT with dopamine (DA). Then, casting method was applied to synthesize a composite film by adding BLZT/DA‐BLZT powders to polyvinylidene fluoride (PVDF) respectively. Results show that DA‐BLZT@PVDF films perform better than BLZT@PVDF films in term of energy storage property and dielectric property. The dielectric constant and energy storage density of DA‐BLZT@PVDF films were all higher than that of BLZT@PVDF films and the dielectric loss was lower than BLZT@PVDF films. X‐Ray Diffraction (XRD) demonstrated the typical perovskite structure was existing in BLZT powder. TEM and SEM also showed that the surface of BLZT powder was successfully coated with DA and uniformly dispersed in PVDF. This research provided an avenue to significantly improve the electrical properties of composite films. Abstract : BaLaZrTiO3 (BLZT) powder was obtained by hydrothermal method and then coated with dopamine (DA). Casting method was applied to synthesize a composite film by adding BLZT/DA‐BLZT powders to polyvinylidene fluoride (PVDF) respectively. Results show that DA‐BLZT@PVDF films perform better than BLZT@PVDF films in term of energy storage property and dielectric property. The dielectric constant and energy storage density of DA‐BLZT@PVDF films were all higher than that of BLZT@PVDF films and the dielectric loss was lower than BLZT@PVDF films.